Diet Protein Content and Individual Phenotype Affect Food Intake and Protein Appetence in Rats. Issue 5 (9th March 2021) - Champeil-Potokar, Gaëlle; Crossouard, Lucas; Jérôme, Nathalie; Ouali, Christian; Darcel, Nicolas; Davidenko, Olga; Rampin, Olivier; Bombail, Vincent; Denis, Isabelle
ABSTRACT: Background: A low-protein diet can induce compensatory intake of excess energy. This must be better evaluated to anticipate the obesogenic risk that may result from the dietary recommendations for reducing animal protein consumption. Objectives: We aimed to further characterize the behavioral and physiological responses to a reduction in dietary protein and to identify the determinants of protein appetite. Methods: Thirty-two male Wistar rats [4 wk old, (mean ± SEM) 135 ± 32 g body weight] were fed a low-protein (LP; 6% energy value) or normal-protein (NP; 20%) diet for 8 wk. Food intake and body mass were measured during the entire intervention. During self-selection sessions after 4 wk of experimental diets, we evaluated rat food preference between LP, NP, or high-protein (HP; 55%) pellets. At the end of the experiment, we assessed their hedonic response [ultrasonic vocalizations (USVs)] and c-Fos neuronal activation in the olfactory tubercle and nucleus accumbens (NAcc) associated with an LP or HP meal. Results: Rats fed an LP diet had greater food intake (24%), body weight (5%), and visceral adiposity (30%) than NP rats. All LP rats and half of the NP rats showed a nearly exclusive preference for HP pellets during self-selection sessions, whereas the other half of the NP rats showed no preference. This suggests that the appetite for proteins is driven not only by a low protein status but also by individual traits in NP rats. LP or HP meal induced similar USV emission and similar neuronal activation in the NAcc in feed-deprived LP and NP rats, showing no specific response linked to protein appetite. Conclusions: Protein appetite in rats is driven by low protein status or individual preferences in rats receiving adequate protein amounts. This must be considered and further analyzed, in the context of current recommendations for protein intake reduction.